Ecovoltaics and grassland responses to solar energy co-location - Sturchio, Matthew Anders, author; Knapp, Alan K., advisor; Ocheltree, Troy, committee member; Schipanski, Meagan, committee member; Mueller, Nathan, committee member (Colorado State University. Libraries, 2024)
The mitigation of climate change requires a transition to renewable sources of energy, and of all available options solar photovoltaic (PV) energy generation has the greatest potential to reduce CO2 emissions by the year 2030. Even so, ground mounted PV is land use intensive, and ideal locations for solar development often overlap with sensitive natural ecosystems and highly productive agricultural land. A scalable approach with potential to alleviate the land use tension created by solar development is the co-location of PV arrays and grassland ecosystems. While this approach has many positive implications for land sparing, the ecological consequences of PV presence above grassland ecosystems are not well understood. In this dissertation I discuss how the unique microenvironments created by PV arrays alter patterns of productivity, physiological response, and forage quality in a semi-arid grassland in Colorado, USA. I also outline a new approach to PV development, Ecovoltaics, that is informed by several fundamental ecological concepts. An Ecovoltaic approach to solar development co-prioritizes energy generation and ecosystem services by intentional design and management through all aspects of array development. With this work, I hope to inform a more sustainable future for solar energy.
Keywords: ecophysiology; grasslands; agrivoltaics; sustainability; ecovoltaics